Dimensions of self-concept between girl’s students expected to graduate from the Faculty of Physical Education and Sports Science due to the integrated them in practical courses in sports - Harafsheh, Ibrahim Mohammad (International Journal of Psychosocial Rehabilitation, 2020)
This study aimed to get the dimensions of the concept of self in the female students expected to graduate from the Faculty of Physical Education and Sports Sciences due to their integration with practical courses in sports. The sample of the study consisted of (30) female students of the Faculty of Physical Education and Sports Sciences, who are expected to graduate in the academic year (2019/2020). In order to collect the necessary data, a mean measure of the self-concept introduced by Wahhabi (1999) was used to suit the Jordanian environment, after the sample responded to the Measure data, it was returned from the students and statistical processors were performed to arrive at the study's results, using arithmetic averages and standard deviation. The study's results refer that the order of the dimensions of the concept of the self as seen by the sample members is as follows: First, self-acceptance, after that personality, after that self-criticism, then moral self-respect, and then family self-respect. the researchers recommend that, in light of the results of the study, the members of the teaching staff of the faculties of sports education in Jordan hold workshops and awareness-raising courses for students practicing sports activities to demonstrate the importance of the concept of self and how to make similar studies to compare the concept of self between males and females, especially those who engage in sports activities or between scientific and human specialties.